Intermittent Ethanol during Adolescence Leads to Lasting Behavioral Changes in Adulthood and Alters Gene Expression and Histone Methylation in the PFC - Wolstenholme, Jennifer T.; Mahmood, Tariq; Harris, Guy M.; Abbas, Shahroze; Miles, Michael F. (Frontiers in Molecular Neuroscience, 2017)
Adolescents primarily consume alcohol in binges, which can be particularly harmful to the developing frontal cortex and increase risk for an adult alcohol use disorder. We conducted a study investigating immediate and long lasting changes to the PFC transcriptome to determine the molecular mechanisms underlying adult ethanol behavioral sensitivity following binge ethanol in adolescence. DBA/2J mice were orally dosed with 4 g/kg ethanol intermittently from day 29 to 42. Adolescent mice were tested for anxiety-like behavior and ethanol sensitivity using the loss of righting reflex task. As adults, mice were tested for cognitive changes using the novel object recognition task, ethanol-induced anxiolysis and ethanol sensitivity. Adolescent binge ethanol altered ethanol sensitivity in young mice and led to lasting memory deficits in the object recognition test and greater ethanol sensitivity in adulthood. Using genomic profiling of transcripts in the PFC, we found that binge ethanol reduced myelin-related gene expression and altered chromatin modifying genes involved in histone demethylation at H3K9 and H3K36. We hypothesize that ethanol’s actions on histone methylation may be a switch for future transcriptional changes that underlie the behavioral changes lasting into adulthood.